The Unfortunate Demise of Police Education. Issue 4 (1st October 2016) - Cordner, Gary
Abstract : This essay takes the position that American society and its police would benefit from a robust system of university-based police education. This is not a new idea but rather an old one never realized. Unfortunately, though we were on a path toward developing just such an enterprise 50 years ago, along came criminal justice, the monster that ate police education.